The Enlightenment teacher Antonín Borový and music in the light of the Zlatá Koruna school chronicle (Theatrum historiae, 2023)
The turn of the 18th and 19th centuries was influenced by extensive educational reforms carried out under the rule of the Austrian Empress Maria Theresa. A ’trivial school’ founded according to the newly introduced methods was established by the abbot Bohumír Bylanský in the Cistercian monastery of Zlatá Koruna as early as in 1772. After ten years, Antonín Borový was appointed as a teacher and from then on he worked at Zlatá Koruna until his death in 1832. Borový was very active in the field of literature and music, and wrote three books of Czech short stories. As he was responsible for music in the church, he created a remarkable music collection consisting of more than 400 music manuscripts; 40 pieces were even written by Borový himself. He kept a German class register in which he began to note the political affairs of the period, climatic rarities, and local festivities. These notes also contain descriptions of significant visits, festivities, and the course of the liturgical year in Zlatá Koruna, including their musical accompaniment and the rewards, both financial and in kind, provided for the teacher’s services. Borový’s activity shows how the above-mentioned educational reforms influenced even a small remote village in South Bohemia.
Keywords: Antonín Borový; teacher; music; Zlatá Koruna; education reforms; liturgy; Enlightenment